Specification Discrepancies to Economic Usury: A Critical Evaluation of Online 'Money Bouquet' Transactions - Yuniar, Sinta; Adhkar, Shohibul (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2023)
Abstract: Buying and selling money buckets online poses many problems. Discrepancies in the specifications of goods that have been agreed between customers and sellers with the results are often encountered. Sellers also often experience problems, such as unilateral cancellation by the buyer. This article will examine the practice of buying and selling money buckets with an order system carried out at the online shop @Meikagallery_. This article is a field research that uses qualitative research methods. Data is obtained through observation, interviews, and documentation conducted on the owner of the money bucket buying and selling business. The data is then analyzed using an emperical juridical approach based on the provisions of Law Number 8 of 1999 concerning Consumer Protection Law and based on Fiqh Mua'malah. The result of this study is that the practice of buying and selling money buckets in the order system on the @Meikagallery_ account is not in accordance with applicable norms. Based on Law Number 8 of 1999 concerning Consumer Protection, non-compliance with the promised specifications of goods and results is a violation of positive legal norms and Islamic law. And when viewed from Fiqh Mua'malah 'aqad Istithnā' becomes void because it cannot fulfill the order according to the agreement.The transaction is also invalid because it contains an element of usury, where the buyer is charged an additional fee in exchanging money.This article provides an overview of how to ideally buy and sell a bouquet of money online, so that sellers and buyers avoid elements that are not allowed in state regulations and Islam.Abstrak: Jual-beli bucket uang secara online menimbulkan banyak masalah. Ketidaksesuaian spesifikasi barang yang telah disepakati antara pelanggan dan penjual dengan hasil produk merupakan hal yang sering ditemui. Sementara, penjual juga sering mengalami masalah, seperti pembatalan sepihak yang dilakukan oleh pembeli. Artikel ini akan mengkaji praktik jual-beli bucket uang dengan sistem pesanan yang dilakukan pada online shop @Meikagallery_. Artikel ini penelitian lapangan (field research) yang menggunakan metode penelitian kualitatif. Data diperoleh melalui observasi, wawancara mendalam, dan dokumentasi yang dilakukan pada pemilik usaha dan pembeli bucket uang. Data kemudian dianalisis menggunakan pendekatan yuridis emperis berdasarkan ketentuan Undang-Undang Nomor 8 Tahun 1999 Tentang Hukum Perlindungan Konsumen dan berdasarkan dengan Fiqih Mua’malah. Hasil dari penelitian ini menunjukkan bahwa praktik kegiatan jual beli bucket uang dalam sistem pesanan pada akun @Meikagallery_ tidak sesuai dengan norma yang berlaku. Berdasarkan Undang-Undang Nomor 8 tahun 1999 tentang Perlindungan Konsumen, tidak sesuainya spesifikasi barang yang dijanjikan dan hasil produk merupakan pelanggaran terhadap norma hukum positif dan hukum Islam. Jika dilihat dari Fiqih Mua’malah, ‘aqad Istithnā’ menjadi batal karena tidak terpenuhinya pesanan sesuai perjanjian. Transaksi juga menjadi tidak sah karena mengandung unsur riba, di mana pembeli dikenakan biaya tambahan dalam penukaran uang. Artikel ini memberikan gambaran bagaimana idealnya jual beli buket uang secara online, agar penjual dan pembeli terhindar dari unsur yang tidak diperbolehkan dalam peraturan negara maupun hukum Islam.